Pretending Ignorance Is Bliss: Competing Insurers with Heterogeneous Informational Advantages - Abrardi, Laura; Colombo, Luca; Tedeschi, Piero (Review of Financial Studies, 2025)
Abstract The availability of big data and analytics expertise provides insurers with informational advantages over policyholders in estimating risk. We study competition between heterogeneously informed insurers, showing that their information may or may not be revealed in equilibrium. We find that all equilibria are profitable and that noninformative equilibria entail risk pooling and possibly efficiency. In informative equilibria, the signaling problem interacts with the screening problem that arises endogenously from insurers’ revelation of information, implying underinsurance. Our main insights are robust to changes in insurers’ information precision and market concentration and to the presence of two-sided asymmetric information and withdrawable contracts.